2002
DOI: 10.1007/s11912-002-0023-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of C-reactive protein as a prognostic indicator in advanced cancer

Abstract: C-reactive protein (CRP) is a nonspecific but sensitive marker of inflammation. Interleukin-6 (IL-6), IL-1, and tumor necrosis factor alpha induce the synthesis of CRP in hepatocytes. Increased CRP level is considered to be an important risk factor for atherosclerosis, myocardial infarction, peripheral vascular disease, and ischemic stroke. It is positively correlated with weight loss, anorexia-cachexia syndrome, extent of disease, and recurrence in advanced cancer. Its role as a predictor of survival has been… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
197
2
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 266 publications
(210 citation statements)
references
References 53 publications
8
197
2
3
Order By: Relevance
“…As Il-6 is known to inhibit the activity of lipoprotein lipase, a key regulatory enzyme for triglyceride clearance from plasma, increased levels of its surrogate CRP were positively correlated with the paraneoplastic inflammatory syndrome, leading to weight loss cachexia (Mahmoud and Rivera, 2002). Besides melanoma (Tartour et al, 1994;Tartour et al, 1996), high CRP serum levels are known to indicate shorter median survival in patients suffering from other tumours such as renal cell carcinoma (Blay et al, 1992) or colorectal carcinoma (Gough et al, 1996;Nozoe et al, 1998;Mahmoud and Rivera, 2002).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As Il-6 is known to inhibit the activity of lipoprotein lipase, a key regulatory enzyme for triglyceride clearance from plasma, increased levels of its surrogate CRP were positively correlated with the paraneoplastic inflammatory syndrome, leading to weight loss cachexia (Mahmoud and Rivera, 2002). Besides melanoma (Tartour et al, 1994;Tartour et al, 1996), high CRP serum levels are known to indicate shorter median survival in patients suffering from other tumours such as renal cell carcinoma (Blay et al, 1992) or colorectal carcinoma (Gough et al, 1996;Nozoe et al, 1998;Mahmoud and Rivera, 2002).…”
Section: Discussionmentioning
confidence: 99%
“…Besides melanoma (Tartour et al, 1994;Tartour et al, 1996), high CRP serum levels are known to indicate shorter median survival in patients suffering from other tumours such as renal cell carcinoma (Blay et al, 1992) or colorectal carcinoma (Gough et al, 1996;Nozoe et al, 1998;Mahmoud and Rivera, 2002). Thus, CRP is not exclusively increased in melanoma.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the presence and the magnitude of a systemic inflammatory response, as evidenced by increased circulating concentrations of C-reactive protein, is a prognostic factor independent of age, stage, performance status, weight-loss and hypoalbuminaemia in patients with advanced cancer including non-small-cell lung cancer (NSCLC) (Martin et al, 1999;O'Gorman et al, 2000;Mahmoud and Rivera, 2002;Scott et al, 2002).…”
mentioning
confidence: 99%
“…Previous studies have established the prognostic importance of the systemic inflammatory response, as evidenced by an elevated circulating C-reactive protein concentration, in patients with advanced solid tumours (O'Gorman et al, 2000;Mahmoud and Rivera, 2002;Maltoni et al, 2005) including breast cancer (Albuquerque et al, 1995;Zhang and Adachi, 1999). Recently, we have shown that, using established cutoffs, a combination of an elevated C-reactive protein and hypoalbuminaemia, the Glasgow Prognostic score (GPS) has prognostic value, independent of stage and performance status, in patients with inoperable non-small-cell lung cancer (Forrest et al, 2003(Forrest et al, , 2004(Forrest et al, , 2005.…”
mentioning
confidence: 99%